German economy: Industry struggles to shake of the crisis - Claus Michelsen; Marius Clemens; Max Hanisch; Simon Junker; Laura Pagenhardt; Thore Schlaak (DIW Weekly Report, 2019)
The German economy remains weak as of the fourth quarter of 2019. However, although industrial production is continuing its downward trend, there are signs of a slow recovery. The manufacturing sector is likely to expand production gradually beginning in 2020; therefore, it is less likely the recession in the industry will affect the service sector and construction industry. These sectors are profiting from strong demand from private households, which is supported by the strong labor market and fiscal stimuli. Thus, after growing by 0.5 percent this year, GDP is likely to increase more strongly in 2020 and 2021, by 1.2 and 1.4 percent, respectively
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook